Doping Effects on Magnetic and Electronic Transport Properties in BaZn2As2 - Guoqiang Zhao; Gangxu Gu; Shuai Yang; Yi Peng; Xiang Li; Kenji M. Kojima; Chaojing Lin; Xiancheng Wang; Timothy Ziman; Yasutomo J. Uemura; Bo Gu; Gang Su; et al. (Crystals)
Novel diluted magnetic semiconductors derived from BaZn2As2 are of considerable importance owing to their elevated Curie temperature of 260 K, the diversity of magnetic states they exhibit, and their prospective applications in multilayer heterojunctions. However, the transition from the intrinsic semiconductor BaZn2As2 (BZA) to its doped compounds has not been extensively explored, especially in relation to the significant intermediate compound Ba(Zn,Mn)2As2 (BZMA). This study aims to address this gap by performing susceptibility and magnetization measurements, in addition to electronic transport analyses, on these compounds in their single crystal form. Key findings include the following: (1) carriers can significantly modulate the magnetism, transitioning from a non-magnetic BZA to a weak magnetic BZMA, and subsequently to a hard ferromagnet (Ba,K)(Zn,Mn)2As2 with potassium (K) doping to BZMA; (2) two distinct sets of metal-insulator transitions were identified, which can be elucidated by the involvement of carriers and the emergence of various magnetic states, respectively; and (3) BZMA exhibits colossal negative magnetoresistance, and by lanthanum (La) doping, a potential n-type (Ba,La)(Zn,Mn)2As2 single crystal was synthesized, demonstrating promising prospects for p-n junction applications. This study enhances our understanding of the magnetic interactions and evolutions among these compounds, particularly in the low-doping regime, thereby providing a comprehensive physical framework that complements previous findings related to the high-doping region.